2023
DOI: 10.47703/ejebs.v1i67.186
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Environmental Behavior and Household Waste Sorting in Kazakhstan: an Empirical Analysis

Abstract: Climate change, deterioration of nature, pollution - all these have led to the fact that ecological behaviour has become a necessity for the conservation of nature and its resources. Pro-environmental behaviour is one of the most important factors for sustainable development. Thus, from year to year, pro-environmental behaviour becomes an important subject of discussion for many scientists and government bodies. The purpose of this study is to determine the level of pro-environmental behaviour among the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…It was found that stakeholders, society and consumers in Kazakhstan do not demonstrate a high level of engagement in environmentally-friendly behavior. This issue has been extensively studied by the authors previously (Zhidebekkyzy et al, 2022), which revealed that among the inhibiting factors for the development of environmental behavior among the population are low awareness levels and infrastructural barriers, particularly in the regions of Kazakhstan (Zhidebekkyzy et al, 2023). The low readiness level of government and financial institutions can be attributed to the absence of legislative documents regulating circular economy practices at the moment.…”
Section: Figure 1 Assessing the Implementation Level Of Circular Econ...mentioning
confidence: 99%
“…It was found that stakeholders, society and consumers in Kazakhstan do not demonstrate a high level of engagement in environmentally-friendly behavior. This issue has been extensively studied by the authors previously (Zhidebekkyzy et al, 2022), which revealed that among the inhibiting factors for the development of environmental behavior among the population are low awareness levels and infrastructural barriers, particularly in the regions of Kazakhstan (Zhidebekkyzy et al, 2023). The low readiness level of government and financial institutions can be attributed to the absence of legislative documents regulating circular economy practices at the moment.…”
Section: Figure 1 Assessing the Implementation Level Of Circular Econ...mentioning
confidence: 99%